Structural, compositional and functional properties of Sb-doped Mg2Si synthesized in Al2O3-crucibles. Issue 84 (26th August 2016) - Sakamoto, Tatsuya; Famengo, Alessia; Barison, Simona; Battiston, Simone; Boldrini, Stefano; Ferrario, Alberto; Fiameni, Stefania; Iida, Tsutomu; Takanashi, Yoshifumi; Fabrizio, Monica
Abstract : Dense Sb-doped Mg2 Si materials were obtained with a cheap and fast process. An extensive characterization was carried out to study the effects of Sb doping and other secondary phases on the stability and functional properties of n-type Mg2 Si1− x Sb x . Abstract : Magnesium silicide (Mg2 Si) is a promising candidate for thermoelectric energy conversion due to its low toxicity, the abundance of its raw constituents and its low density, allowing manufacturing of light, sustainable and relatively cheap devices. Mg2 Si needs to be doped in order to increase its efficiency, making this material competitive among materials operating in the intermediate temperature range. In this work, a synthesis procedure based on melting of the raw elements in easily available and cheap Al2 O3 crucibles was developed to obtain polycrystalline Sb doped Mg2 Si materials in a wide range of compositions. Powders from the crushed lumps were consolidated via spark plasma sintering and then thermally annealed to obtain dense pellets of Sb:Mg2 Si with Sb = 0.0, 0.1, 0.3, 0.5, 0.7, 1.0 and 1.5 at%. The effects of Sb doping and of the synthesis and sintering technique on composition, morphology and stability of n-type Mg2 Si are discussed. Transport properties (Seebeck coefficient, electrical and thermal conductivity, charge carrier density) were evaluated in order to elucidate the composition–property relationship within this material system and find the optimal doping amount to optimize its thermoelectric properties.